Analisis Dokumen dan Implementasi Kurikulum Merdeka Belajar Kampus Merdeka di Universitas Negeri Padang: Studi Kasus Teknik Elektro Industri - Sardi, Juli; Habibullah, Habibullah; Gistituati, Nurhizrah; Betri, Alwen; Yuliana, Devi Faizah (Jurnal Pendidikan Teknik Elektro, 2024)
The issuance of Permendikbud No. 3 of 2020 concerning National Higher Education Standards (SN-DIKTI) encourages Study Programs in Higher Education to review their curriculum. The implementation of the MBKM program for Undergraduate and Applied Undergraduate Programs has an impact on the learning process where students are given the right to take their studies in three semesters outside their study program. The D4 Industrial Electrical Engineering Study Program at Padang State University is one of the study programs that has implemented the MBKM curriculum since 2021. However, so far no evaluation has been carried out either of the completeness of the curriculum documents or the implementation of the MBKM curriculum itself. The research method used in this research is a qualitative method with a descriptive approach. Data collection techniques in qualitative research are observation, interviews, and documentation studies. The results obtained in this study are the completeness of the 81.8% Industrial Electrical Engineering D4 Study Program curriculum documents with details of 54.5% of the curriculum documents can be shown in writing and 27.3% cannot be shown in writing. The remaining 18.2% of curriculum documents do not exist / complete. Until now, the D4 Industrial Electrical Engineering Study Program has only carried out 1 type of MBKM activity / activity, namely Internships / Work Practices. In 2022 the number of students who participated in MBKM Internships / Work Practices amounted to 99 out of 458 students with a percentage of 21.62%. Meanwhile, for 2023 the number of students who participated in Internships / Practical Work was 102 out of 364 students with a percentage of 28.02%. Based on these findings, it is concluded that the completeness of documents and the implementation of MBKM in the D4 Industrial Electrical Engineering Study Program has gone well and is in accordance with applicable regulations.